Burnout among faculty physicians in an academic health science centre - Wright, J; Khetani, N; Stephens, D (Oxford University Press, 2011)
BACKGROUND: Burnout experienced by physicians is concerning because it may affect quality of care. OBJECTIVE: To determine the frequency of burnout among physicians at an academic health science centre and to test the hypothesis that work hours are related to burnout. METHODS: All 300 staff physicians, contacted through their personal e-mail, were provided an encrypted link to an anonymous questionnaire. The primary outcome measure, the Copenhagen Burnout Inventory, has three subscales: personal, work related and patient related. RESULTS: The response rate for the questionnaire was 70%. Quantitative demands, insecurity at work and job satisfaction affected all three components of burnout. Of 210 staff physicians, 22% (n=46) had scores indicating personal burnout, 14% (n=30) had scores indicating work-related burnout and 8% (n=16) had scores indicating patient-related burnout. The correlation between total hours worked and total burnout was only 0.10 (P=0.14) DISCUSSION: Up to 22% of academic paediatric physicians had scores consistent with mild to severe burnout. A simple reduction in work hours is unlikely to be successful in reducing burnout and, therefore, quantitative demands, job satisfaction and work insecurity may require attention to address burnout among academic physicians.